Defining the Limits of Greater India. Issue 8 (17th April 2019) - Meng, Jun; Gilder, Stuart A.; Wang, Chengshan; Coe, Robert S.; Tan, Xiaodong; Zhao, Xixi; He, Kuang
Abstract: Greater India comprises a part of the Indian plate that subducted under Asia to help form the Tibetan Plateau. Defining the size of the Greater India is thus a key constraint to model the India‐Asia collision, growth of the plateau, and the tectonic evolution of the Neo‐Tethyan realm. We report Early Cretaceous paleomagnetic data from the central and eastern Tethyan Himalaya that yield paleolatitudes consistent with previous Early Cretaceous paleogeographic reconstructions. These data suggest Greater India extended at least 2, 675 ± 720 and 1, 950 ± 970 km farther north from the present northern margin of India at 83.6°E and 92.4°E, respectively. An area of lithosphere ≥4.7 × 10 6 km 2 was consumed through subduction, thereby placing a strict limit on the minimum amount of Indian lithosphere consumed since the breakup of Gondwanaland. Plain Language Summary: Greater India is part of the Indian plate, subsequently subducted under Asia, that helped create the Tibetan Plateau. The amount of Greater Indian crust therefore plays a critical role to address key problems in continental geodynamics. To what extent can continental crust be subducted? How much crust was derived from horizontal shortening of existing crust? How much of Tibet was created by subducted buoyant, continental crust? We provide paleomagnetic evidence that defines the minimum size of Greater India. Our data show that a lithospheric area of ≥4.7 × 10 6 km 2 was subducted, which supports the notion that the growth of Tibetan Plateau in the Cenozoic occurred by adding buoyant material to its base. Key Points: Early Cretaceous paleomagnetic data from the central and eastern Tethyan Himalaya yield paleolatitudes of 30.5 ± 4.9 °S and 39.6 ± 7.6 °S Greater India extended 2, 675 ± 720 and 1, 950 ± 970 km farther north from the present northern margin of India at 83.6 °E and 92.4 °E at 130 Ma An area of ≥ 4.7 × 10 6 km 2 of Greater Indian lithosphere was consumed by subduction